2005
DOI: 10.1111/j.1399-5618.2005.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐drug interactions as a determinant of elevated lithium serum levels in daily clinical practice

Abstract: Objective:  Lithium is a drug with a narrow therapeutic window. Concomitantly used medication is a potentially influencing factor of lithium serum concentrations. We conducted a multicentre retrospective case‐control study with the aim of investigating lithium‐related drug interactions as determinants of elevated lithium serum levels in daily clinical practice. Methods:  Cases were patients with an increase of at least 50% in lithium serum concentrations resulting in an elevated lithium serum level of at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Finally, we have not been able to correct for other important patient characteristics that have previously been demonstrated to be related to lithium serum levels, such as comorbidity, current mood phase of BD, diarrhea, vomiting, infections or renal insufficiency, concomitantly used medication, pregnancy, changes in diet, alcohol use or weight, and higher rates of perspiration due to exercise or visits to saunas (2, 36–38).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have not been able to correct for other important patient characteristics that have previously been demonstrated to be related to lithium serum levels, such as comorbidity, current mood phase of BD, diarrhea, vomiting, infections or renal insufficiency, concomitantly used medication, pregnancy, changes in diet, alcohol use or weight, and higher rates of perspiration due to exercise or visits to saunas (2, 36–38).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions involving drugs with a narrow therapeutic range (e.g., warfarin, cyclosporine, clozapine, lithium, digoxin, phenytoin, and theophylline) have more frequent and serious clinical consequences than those involving drugs with a wide therapeutic range [84][85][86][87]. The dosage of the interacting drug may also be critical [88].…”
Section: Main Risk Factors For Adverse Drug Interactionsmentioning
confidence: 99%
“…For example, it was shown that even a simple switch from one ACE-I to another (fosinopril to lisinopril) can provoke lithium toxicity (26). Whatever the exact mechanism may be, an increase in the serum lithium level is often observed with the introduction of ACE-I or AT 1 blockers (7,22). Once the lithium concentration has reached equilibrium, such a drug combination can be relatively safely maintained, although caution is still needed when the dose of ACE-I/AT 1 blockers is increased (23).…”
Section: Discussionmentioning
confidence: 99%